El déficit del magnesio en la producción del cultivo de arroz (Oryza sativa L.) - Navarrete Tapia, José Daniel (2024)
Rice (Oryza sativa L.) is the basic food for the world's population and the most important crop, considering the extent of the planting area and the number of people, which depends on its production. The objective was to define the importance of magnesium in the cultivation of rice (Oryza sativa L.). This document was developed through the compilation of diverse information for research purposes from various websites, scientific articles, sources and bibliographic repositories that are accessible through digital platforms. The conclusions determined that the symptoms of Mg deficiency in plants include interveinal chlorosis and red spots on old leaves. Additionally, high levels of magnesium deficiency make the leaves wavy and drooping due to the expansion of the angle between the leaf blade and sheath; Intervein chlorosis is characterized by a yellow-orange color on the lower leaves. Among the methods that allow avoiding magnesium deficiency in rice cultivation are chemical fertilization, stubble burning, incorporation of residues into the soil, soil analysis, physicochemical properties and monitoring chlorophyll levels, the photosynthetic rate or synthesis of proteins.